Restoration of cardiomyogenesis in aged mouse hearts by voluntary exercise - Lerchenmüller, Carolin; Vujic, Ana; Mittag, Sonja; Wang, Annie; Rabolli, Charles P.; Heß, Chiara; Betge, Fynn; Rangrez, Ashraf Yusuf; Chaklader, Malay; Guillermier, Christelle; Gyngard, Frank; Roh, Jason D.; et al. (Circulation, 2022)
Background: - - The human heart has limited capacity to generate new cardiomyocytes and this capacity declines with age. Because loss of cardiomyocytes may contribute to heart failure, it is crucial to explore stimuli of endogenous cardiac regeneration to favorably shift the balance between loss of cardiomyocytes and the birth of new cardiomyocytes in the aged heart. We have previously shown that cardiomyogenesis can be activated by exercise in the young adult mouse heart. Whether exercise also induces cardiomyogenesis in aged hearts, however, is still unknown. Here, we aim to investigate the effect of exercise on the generation of new cardiomyocytes in the aged heart. - - Methods: - - Aged (20-month-old) mice were subjected to an 8-week voluntary running protocol, and age-matched sedentary animals served as controls. Cardiomyogenesis in aged hearts was assessed on the basis of 15N-thymidine incorporation and multi-isotope imaging mass spectrometry. We analyzed 1793 cardiomyocytes from 5 aged sedentary mice and compared these with 2002 cardiomyocytes from 5 aged exercised mice, followed by advanced histology and imaging to account for ploidy and nucleation status of the cell. RNA sequencing and subsequent bioinformatic analyses were performed to investigate transcriptional changes induced by exercise specifically in aged hearts in comparison with young hearts. - - Results: - - Cardiomyogenesis was observed at a significantly higher frequency in exercised compared with sedentary aged hearts on the basis of the detection of mononucleated/diploid 15N-thymidine-labeled cardiomyocytes. No mononucleated/diploid 15N-thymidine-labeled cardiomyocyte was detected in sedentary aged mice. The annual rate of mononucleated/diploid 15N-thymidine-labeled cardiomyocytes in aged exercised mice was 2.3% per year. This compares with our previously reported annual rate of 7.5% in young exercised mice and 1.63% in young sedentary mice. Transcriptional profiling of young and aged exercised murine hearts and their sedentary controls revealed that exercise induces pathways related to circadian rhythm, irrespective of age. One known oscillating transcript, however, that was exclusively upregulated in aged exercised hearts, was isoform 1.4 of regulator of calcineurin, whose regulation and functional role were explored further. - - Conclusions: - - Our data demonstrate that voluntary running in part restores cardiomyogenesis in aged mice and suggest that pathways associated with circadian rhythm may play a role in physiologically stimulated cardiomyogenesis.
Gesehen am 03.01.2023